G149 Liver service in a regional paediatric gastroenterology unit in Wessex. (24th May 2017) - Hakizimana, A; Greig, RJE; Lazenbury, A; Brown, SK; Bonduelle, Q; Barnes, C; Wright, M; Afzal, NA
Abstract : Aims: To study the provision of paediatric liver services in a regional centre in the South of England Methods: Children with liver diseases seen in paediatric Hepatology clinics over the last 5 years were included in the study. Details of demographics, underlying diagnosis, investigations and treatments were extracted in a database. Results: There are two paediatric liver clinics in Southampton; one in conjunction with the supra-regional liver centre in London and the other a regional transitional clinic, with 3 consultants (supraregional, regional and transitional), dietetic, specialist nursing support and representation of the national charity Children Liver Disease Foundation in the clinics. Overall 223 children (Median Age: 12.2 years IQR: 6.8–17.1 years) were seen in the services (M:F 54.7:45.3) over the last 5 years (45 patients diagnosed/year). Children were referred from 11 hospitals across the network (Hampshire, Dorset, Wiltshire and Sussex). The most common 3 diagnoses seen in the clinics were Alpha-1-Antitrypsin deficiency (17%), Viral Hepatitides (11.7%) and Autoimmune liver disease (9.9%). With an increasing national incidence, 9.4% of the children presented with fatty liver and 15 patients with liver transplant are seen in the services. Nearly a third of patients graduated from the joint supra-regional clinic to the regional transitional clinic with provision of local radiology, bile duct stenting, bile duct botox and variceal banding services (endoscopic). Conclusions: This study reflects the busy work load of a regional liver paediatric gastroenterology centre in the South of England. The paediatric liver services bridge an important gap between DGHs and supra-regional centres providing family centred specialist care for children with liver diseases, at convenience and closer to their homes. With an increasing new patient referral from DGHs and nearly third of patients transitioning to adult services, the need of a regional hepatology transitional clinic cannot be underestimated which can work in tandem with the joint supra-regional liver clinics providing uninterrupted smooth transition and continuity of care. With these increasing responsibilities, the role of a regional paediatric GI centre needs to be better recognised in managing paediatric liver patients, as currently highlighted in the NHS England specialist liver disease services contract.